Second-Person Arts-Based Action Research for Group Reflection - Victoria L. Dickman-Burnett; Trinity V. Shaya; Isabelle R. Zalat (Journal of Participatory Research Methods)
This brief report discusses the use of second-person arts-based action research in the context of a participatory research team of one mentor researcher and two undergraduate student researchers studying their own relationship with rape culture through arts-based second-person inquiry. The inquiry involved two phases with intentional reflection between each phase. This report outlines how the second-person arts-based approach was used in the group to offer a framework to similar approaches for other groups in their own research practices. Second-person research approaches offer both the reflection of first-person research and the group discussion of second-person research, adding rich reflexive elements to existing participatory research projects. The arts-based elements enhance these processes with creativity and thoughtfulness.